Prediction of future injury in sport: Primary and secondary anterior cruciate ligament injury risk and return to sport as a model - Hewett, T. E. (Journal of Orthopaedic & Sports Physical Therapy, 2017)
Can we predict future events? Biostatisticians might answer with an unequivocal yes and state that logistic regression models do exactly that: they predict the relative risk of an outcome on the basis of logistic regression of multiple independent variables. If this is the case, then which approaches improve predictive capability? We are not attempting to predict individual events in individual athletes. However, certain approaches can improve predictive power.